2021
DOI: 10.3389/fimmu.2021.747357
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of Limbal Stem Cells to Decrease Allogeneic Immune Responses

Abstract: Limbal stem cell (LSC) transplantation is the only efficient treatment for patients affected by LSC deficiency (LSCD). Allogeneic LSC transplantation is one of the most successful alternative for patients with bilateral LSCD. Nevertheless, the high variability of the human leukocyte antigens (HLA) remains a relevant obstacle to long-term allogeneic graft survival. This study characterized the immunologic properties of LSCs and proposed a genetic engineering strategy to reduce the immunogenicity of LSCs and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…One of the strategies proposed to reduce xenograft immunogenicity is the downregulation of swine leukocyte antigen (SLA) class I and class II expression [ 16 ]. A robust silencing of SLA class I and class II expression may decrease the strength of allo- or xenogeneic immune responses by generating an immunologically invisible status of tissues and organs supporting graft survival [ 17 , 18 , 19 ]. The use of PTECs isolated from genetically modified pigs or in vitro genetically modified PTECs may contribute to evaluate the effect of specific genetic modifications in human immune response towards porcine-derived kidneys and to monitor the status and strength of xenogeneic immune response after transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the strategies proposed to reduce xenograft immunogenicity is the downregulation of swine leukocyte antigen (SLA) class I and class II expression [ 16 ]. A robust silencing of SLA class I and class II expression may decrease the strength of allo- or xenogeneic immune responses by generating an immunologically invisible status of tissues and organs supporting graft survival [ 17 , 18 , 19 ]. The use of PTECs isolated from genetically modified pigs or in vitro genetically modified PTECs may contribute to evaluate the effect of specific genetic modifications in human immune response towards porcine-derived kidneys and to monitor the status and strength of xenogeneic immune response after transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…In an allogeneic setting, we have previously demonstrated the possibility of stably silencing the expression of MHC class I and II on complete organs such as the rat kidney, limb, or pig lung. These studies showed the possibility to silence MHC expression on complex 3D structures consisting of a variety of cell types and with different immunogenic potentials [ 16 , 18 , 19 ]. Despite the value of the possibility to evaluate the strength of immune responses towards a specific organ cell type, which may contribute to further clarifying mechanisms of rejection in xenotransplantation, the use of more complex systems may contribute to assessing such responses in a more physiological setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation